Competence Analysis Of Training And Supervision Of Employee Performance - Nainggolan, Tuty (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The research aims to find the relationship between the influence of competence, training, supervision on employee performance simultaneously and how to influence competence, training and work supervision on employee performance partially. The research method with this research approach used is a quantitative approach. This type of research is a quantitative descriptive research. The data collection technique in this research was carried out by: Interviews (interviews). The partial test results show that competency has a positive and significant effect on employee performance at PT. Toyota Astra Motor. The partial test results show that training has a positive and significant effect on employee performance at PT. Toyota Astra Motor. The partial test results show that supervision has a positive and significant effect on employee performance at PT. Toyota Astra Motor. Simultaneous test results show that competency, training and supervision have a positive and significant effect on performance at PT. Toyota Astra Motor. The adjusted R2 coefficient of determination from training and communication explains the employee performance variable of 93.7% and the remaining 6.3% is explained by other independent variables not examined.